MEDITATION IN SCHOOL ADOLESCENTS WHO SIT IN OLYMPIC AND ACCELERATION CLASS - Riska Titis Andriyani; Suhartini Suhartini (Jurnal Keperawatan Diponegoro, 2012)
Background:.Meditation is a state of consciousness in which the individual eliminates environmental stimuli from awareness so that the mind has single focus, producing a state of relaxation and relief from stress. Stress that happen in school environment or education is called academic stress. The purpose of this research was to analize the influence of meditation to academic stress in school adolescents who sit in olympic and acceleration class. Method: The researcher used a experimental quantitative with one-group pre-test and post test design without control group. This research had done to 27 respondents, such as first and second grade of olimpiade class and last grade of acceleration class in SMA N 3 Semarang. The tool that used in this research was Academic Expectations Stress Inventory (AESI) that indicated academic stress from expectations of self and expectations of parents and teacher Data analysis used Paired Sample t-Test. Result and Suggestion: This research showed that 25 respondents (92,59%) had depreciation score of academic stress, 1 respondent (3,70%) had permanent score and 1 respondent (3,70%) increase score of academic stress. Significant score from Paired Sample t-Test showed that 0,000 < α (0,05) so that H0 was aversed and H1 was accepted. This research resulted there was influence of meditation to academic stress in school adolescents who sit in olympic and acceleration class,it is expected in nursing practice and some resorts to use meditation as a self supporting intervention